INFORMATION QUALITY, COMMUNICATION EFFECTIVENESS, TECHNOLOGY QUALITY IN INFLUENCING INTENSION AND ACTUAL USE OF ICT FOR TRACKING ADMINISTRATION OF MALARIA DRUGS IN HEALTH UNITS IN UGANDAN. A DESCRIPTIVE AND CORRELATIONAL STUDY. - Ssegawa, E. James Kiggundu (Student’s Journal of Health Research Africa, 2023)
Background: The purpose of this study is to examine how Information Quality, Communication effectiveness, and Technology quality influence the intention and actual use of ICT in tracking the administration of malaria drugs in health units in Uganda. Methods: Descriptive statistics was engaged to determine the degree and or / extent of occurrence of information quality, communication effectiveness, and technology quality A co-relational research design was used to determine the relationships between them. Analysis of the magnitude of relationship and levels of significance among the variables, Pearson’s cross-product bivariate deviation, and covariance was engaged and regression was used to determine how such variables would influence the intention and actual use of ICT in tracking the administration of malaria drugs in health units. Scope: A survey was conducted on 465 health units in the Masaka, Rakai, Kalungu, and Kampala districts in the central region of Uganda. Findings: Information quality measured in the dimensions of Intrinsic Information Quality (IIQ) (mean = 3.46), Contextual Information Quality (CIQ) (mean = 3.71), Representative Information Quality (RIQ) (mean = 3.77 was rated satisfactory for public and private health units/hospitals; Communication Effectiveness was satisfactory (mean = 3.52) but rated low because of using written documentation during the administration of malaria drugs in health units. Quality of Technology employed during the administration of malaria drugs in health units had a fair performance (mean = 3.12), not very effective because perceptions and attitude towards the ICTs systems by medical staff was very not positive (mean = 2.29), knowledge of the use of ICT systems, (mean = 3.26) and skills (mean = 3.15) were average.